2008
DOI: 10.1080/00016340802179814
|View full text |Cite
|
Sign up to set email alerts
|

Do pregnant women still smoke? A study of smoking patterns among 261,029 primiparous women in Denmark 1997–2005

Abstract: In this nationwide survey, a significant decline in the prevalence of primiparous women who smoked during pregnancy was observed from 1997 to 2005. Despite of this, pregnancy-related smoking prevalence in Denmark is still higher than in the other Nordic countries. Furthermore, the proportion of pregnant smokers was highest among young women, and future smoking cessation programs should bring this subgroup of women into focus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 22 publications
4
45
2
Order By: Relevance
“…However, these values remain far from the goal of 2% during pregnancy given by “Healthy People—2010” [8]. After a decreasing trend, the prevalences of smoking in pregnancy were 11% in Canada in 2005 [9], 16% in Denmark in 2005 (among pregnant nulliparous women) [10], and 20% in Australia in 2004 [11]. An opposite trend was registered in Japan where the prevalence of smoking in pregnancy increased from 5.6% in 1991 to 10% in 2001 [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, these values remain far from the goal of 2% during pregnancy given by “Healthy People—2010” [8]. After a decreasing trend, the prevalences of smoking in pregnancy were 11% in Canada in 2005 [9], 16% in Denmark in 2005 (among pregnant nulliparous women) [10], and 20% in Australia in 2004 [11]. An opposite trend was registered in Japan where the prevalence of smoking in pregnancy increased from 5.6% in 1991 to 10% in 2001 [12].…”
Section: Introductionmentioning
confidence: 99%
“…The number of pregnant women studied in the stratified analyses was rather low, but at the time of enrollment, the frequency of smoking among pregnant women in Denmark was much higher than today (44), making it very difficult to repeat the study. Also, as the study was conducted before the mandatory iodine fortification of salt in Denmark (32), the pregnant women suffered from mild-to-moderate iodine deficiency, which makes iodide transport by NIS or other placental iodide transporters more sensitive to the competitive inhibition by thiocyanate.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The results in the current study showed a quit rate of 24.5% to 32.2% in pregnant smokers and 24.1% to 31.8% in non-pregnant smokers. From 1997 to 2005 an average of 13.4% of the pregnant smokers in Denmark stopped smoking [13]. Compared to these numbers, the effect of the GSP is very high and seems to be an effective intervention for pregnant smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, the prevalence of women smoking at some point during their pregnancy was 16% on average in Denmark [13], which had decreased from 22% in 1997. From 1997 to 2005 there was a markedly higher smoking prevalence for pregnant women under the age of 25 years [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation